2021
DOI: 10.3168/jds.2020-20020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental source of magnesium and inclusion of buffer on ruminal microbial fermentation in continuous culture

Abstract: Magnesium oxide (MgO) is the most common supplemental source of Mg for dairy cows and a proven ruminal alkalizer when supplemented above NRC (2001) recommendations. However, overfeeding MgO may increase feeding costs, whereas the effects of alternative sources of Mg on ruminal fermentation are not well known. Moreover, it is still unclear if Mg supplementation influences the effects of bicarbonate-based buffers on ruminal fermentation. We aimed to evaluate the effect of Mg source on ruminal fermentation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…However, in the present study no treatment effects were observed on OM digestibility resulting in lack of effects on microbial N flow and microbial efficiency. Microbial efficiency of 17.5 g [ 23 ] and 18.4 g of microbial N flow/kg of digested OM [ 24 ] observed in previous studies using similar continuous culture fermenter system with comparable liquid and solid passage rates are in agreement with values observed in this study. In contrast, others reported 34.6 and 22.7 g of microbial N flow/kg of OM truly digested [ 25 , 26 ], respectively.…”
Section: Discussionsupporting
confidence: 91%
“…However, in the present study no treatment effects were observed on OM digestibility resulting in lack of effects on microbial N flow and microbial efficiency. Microbial efficiency of 17.5 g [ 23 ] and 18.4 g of microbial N flow/kg of digested OM [ 24 ] observed in previous studies using similar continuous culture fermenter system with comparable liquid and solid passage rates are in agreement with values observed in this study. In contrast, others reported 34.6 and 22.7 g of microbial N flow/kg of OM truly digested [ 25 , 26 ], respectively.…”
Section: Discussionsupporting
confidence: 91%
“…A dual-flow continuous culture system, as developed by Hoover et al (1976) and described by Arce-Cordero et al (2021b) and Wenner et al (2021), was used for this experiment. The fermentation vessels used had an average volumetric capacity of 1.82 L when filled until the solid effluent outflow port.…”
Section: Dual-flow Continuous Culture System Operationmentioning
confidence: 99%
“…A dual-flow continuous culture system as developed by Hoover et al (1976) and described by Arce-Cordero et al (2021a , 2021b ) was used for this experiment. Artificial saliva was infused continuously ( Weller and Pilgrim, 1974 ) at a rate of 3.1 mL/min into the system and a partial removal of fermentation liquid effluent at 1.55 mL/min, allowed the removal of liquid and solid effluents to be controlled at a rate of 11% and 5.5%/h respectively.…”
Section: Methodsmentioning
confidence: 99%